TARTEEL: SUPPORTING QURAN MEMORIZATION THROUGH INTERACTIVE LEARNING - Sopa Ulkarimah; Tatang Tatang (PROGRES PENDIDIKAN, 2026)
This study explores the effectiveness of the Tarteel application in supporting Quran memorization, focusing particularly on the muroja’ah feature. The research employs a qualitative descriptive approach to understand user experiences, perceptions, and engagement with the application. Data were collected through observations, in-depth interviews, and structured questionnaires, allowing the researcher to capture both objective usage patterns and subjective experiences. Participants included active users of Tarteel with varying levels of memorization proficiency, ensuring insights from both beginner and advanced memorizers. Findings indicate that Tarteel significantly enhances memorization consistency, accuracy, and fluency. The muraja’ah feature enables systematic review of previously memorized verses, while audio playback, Tajweed color coding, and interactive quizzes facilitate multisensory learning. Users reported increased motivation, engagement, and independence in their memorization practices. Additionally, the application fosters a supportive learning community, allowing users to share progress and tips, which enhances social reinforcement and collaborative learning. Despite these benefits, limitations include dependency on a stable internet connection, potential digital distractions, and reduced direct mentorship from teachers. Users must balance application use with traditional guidance to optimize memorization outcomes. Overall, Tarteel proves to be an effective digital tool for complementing conventional Quran memorization methods, supporting structured, interactive, and flexible learning in the modern era.